The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ob01273a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical S–H and O–H insertion reactions from thiols or salicylic acids with diazo esters

Abstract: An electrochemical carbenoid insertion reaction of diazo compounds into C-S and C-O bonds with electricity as oxidant has been reported in this work. In this protocol, this transformation proceeded smoothly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…18 ). 54 The S–H insertion reaction was performed at room temperature under 5 mA constant current in an undivided electrolytic cell equipped with a graphite anode and a graphite cathode using TBAB as the electrolyte and DCE as the solvent. A variety of thiols underwent S–H insertion reactions with diazo esters, giving the desired product in moderate to high yields.…”
Section: Electrosynthesis Of C–s Bondmentioning
confidence: 99%
“…18 ). 54 The S–H insertion reaction was performed at room temperature under 5 mA constant current in an undivided electrolytic cell equipped with a graphite anode and a graphite cathode using TBAB as the electrolyte and DCE as the solvent. A variety of thiols underwent S–H insertion reactions with diazo esters, giving the desired product in moderate to high yields.…”
Section: Electrosynthesis Of C–s Bondmentioning
confidence: 99%
“…However, the costs and toxicity of these metals as well as the ligands involved restrict this traditional methodology, thus making it necessary and attractive to develop metal-free strategies. Recently, Brønsted acid catalysis, Lewis acid catalysis, , photosynthesis, and electrosynthesis have been applied in the O–H insertions successfully (Scheme b), which provide environmentally benign and economical alternatives for this important transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent example, Huang et al used diazoesters in an electrochemical reaction but the diazoester was not electrochemically activated or explored in that work. 11 Careful curation of the literature revealed that there are only a few reports to date demonstrating the generation of carbene anion radicals. The McDonald research group (1986) and later Parker and Bethell et al (1989) reported the electrochemical generation of the diazoalkane radical followed by thermal loss of dinitrogen to form the carbene anion radical.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent example, Huang et al used diazoesters in an electrochemical reaction but the diazoester was not electrochemically activated or explored in that work. 11 …”
Section: Introductionmentioning
confidence: 99%